Проблема змішаної (складної) форми вини у злочинах, при вчиненні яких порушуються права на об’єкти інтелектуальної власності - Харченко, В. Б.; Kharchenko, V. B.; ORCID: http://orcid.org/0000-0002-1214-0313 (Вісник Кримінологічної асоціації України. - 2017. - № 1 (15). - С. 146-158, 2017)
Розглянуто питання щодо змісту та сутності змішаної (складеної) форми вини через характерний для неї розрив цілісного процесу психічної діяльності особи, що відображає єдине ставлення її свідомості і волі до суспільно небезпечного діяння, яке вона вчиняє. Зазначено, що в злочинах у сфері інтелектуальної власності у законодавця при вказівці на ступінь їх суспільної небезпечності відсутня будь-яка альтернатива, він просто має назвати наслідки таких діянь, які їм не властиві, але певним чином пов’язані з порушенням прав на об’єкти інтелектуальної власності.

The features of mens rea of the crimes in the sphere of intellectual property, characterized by a complex mental activity of a guilty party as their commission with a mixed (complex or double) form of guilt. It is alleged about the full support of doctrinal approaches to contradiction of terminology concerning the mental attitude and the need to determine the stated form of guilt as the “complex”. Based on the legislative construction of attacks on personal non-property and (or) exclusive property rights on the objects of intellectual property, we conclude about the feasibility of allocating a certain mental attitude of a person directly to the violation of such rights (action or omission) and on criminal consequences that occurred (material or substantial damage) within one corpus delicti. The author emphasizes on the necessity of classifying the crimes in the field of intellectual property to the category of intentional crimes, since the subject is aware of the dangers of such an abuse, involves infringement of intellectual property rights as a result of the actions and desires it. However, these characteristics of mental activity are considered by the author exclusively to the fact of the violation itself that provides grounds to define the mental attitude of a person to dangerous consequences as both intentional and reckless. The above stated does not exclude the fact that in the case of a crime commission in the sphere of of intellectual property, a person awares not only the social danger of such an infringement of the relevant objects and wishes to violate these rights, but also gas a will or deliberately assumes the property damage of the holder’s rights to some tune, large or especially large scale or significant damage. Thus, the legislator determines the features that provide to disciplinary, civil and legal or administrative delicts the appropriate degree of public danger, as a rule, establishing qualified consequences of such acts. It is noted that the legislator in most cases has no alternative to indicate the degree of social danger of a crime in the sphere of intellectual property and its difference from other similar or identical offenses, than to point out these effects of the act, which are unusual, but somehow related with its commission. Therefore, the violation of the right on intellectual property objects is an independent, self-sufficient and structured act of behavior of a person, who is objectively characterized by an act (action or omission), the result – violation of personal nonproperty and (or) exclusive property rights to objects of intellectual property and the cause and effect relationship. The mental activity of a person reflects directly to this act of behavior, the attitude of its consciousness and will in the form of intent, namely characterizes the act from the subjective side. The features of infringements to intellectual property in the form of causing material or significant damage, which certainly related to the commission of such acts, but are not included into its structure and are not covered by its content, require additional independent determination of intellectual and volitional moments of person’s mental attitude to them. This attitude can be both intentional and reckless.

Рассматриваются вопросы содержания смешанной (сложной) формы вины в связи с характерным для нее разрывом целостного процесса психической деятельности лица, отражающим единое ее отношение сознания и воли к общественно опасному деянию, которое оно совершает. Указывается, что в преступлениях в сфере интеллектуальной собственности у законодателя отсутствует какая-либо альтернатива указать на степень их общественной опасности, нежели предусмотреть последствия таких деяний, которые им несвойственны, но определенным образом связаны с нарушением прав на объекты интеллектуальной собственности.
Problem of mixed (complex) form of guilt in crimes violating the rights on intellectual property objects
Проблема смешанной (сложной) формы вины в преступлениях, при совершении которых нарушаются права на объекты интеллектуальной собственности
Харченко, В. Б. Проблема змішаної (складної) форми вини у злочинах, при вчиненні яких порушуються права на об’єкти інтелектуальної власності / Вадим Борисович Харченко // Вісник Кримінологічної асоціації України. - 2017. - № 1 (15). - С. 146-158.
Kharchenko, V. B. (2017), “Problem of mixed (complex) form of guilt in crimes violating the rights on intellectual property objects” [Problema zmishanoi (skladnoi) formy vyny u zlochynakh, pry vchynenni yakykh porushuiutsia prava na ob’iekty intelektualnoi vlasnosti], Visnyk Kryminolohichnoi asotsiatsii Ukrainy, No. 1, pp. 146–158.
Keywords: Кримінальне право. Criminal Law. Уголовное право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; подвійна (змішана) форма вини; складена форма вини; психічна діяльність; злочини у сфері інтелектуальної власності; double (mixed) form of guilt; compiled form of guilt; mental activity; crimes in the sphere of intellectual property; змішана форма вини; двойная (смешанная) форма вины; составная форма вины; психическая деятельность; преступления в сфере интеллектуальной собственности; смешанная форма вины